Penerapan Sistem Informasi Odoo ERP pada UMKM Toko Erika - Jeremy Kurniawan; Mira Ziveria (UNIVERSITAS KALBIS, 2022)
Erika's shop is a small business that sells various kinds of daily products in the form of groceries, kitchens, toiletries, soft drinks, snacks, gas, medicines and others. This shop is located on Jalan Kwitang Kembang X, Central Jakarta. In running a business in the form of a small shop, Erika's Shop is still run by a manual system where bookkeeping is in recording purchases, sales and storage to customers and suppliers. This causes several obstacles that greatly affect the running of business processes such as loss of data on purchases and sales of goods. So from this problem a system is created that can help business processes run well and efficiently by implementing Odoo ERP using the Waterfall method. The purpose of this research is to make it easier for Erika shop owners to run business processes and increase the accuracy of data recording with the Odoo ERPi system in the form of Purchasing, Sales and Inventory modules.